Observer based dynamic control model for bilaterally controlled MU-lapa robot: Surgical tool force limiting - Branesh M. Pillai; Chumpon Wilasrusmee; Jackrit Suthakorn (Institute of Advanced Engineering and Science, 2020)
During laparoscopic surgeries, primary surgical tool insertion is the demanding and strenuous task. As the surgeon is unaware of the type of the tissue and associated parameters to conduct the insertion, therefore, to ease the procedure, the movement of the surgical tool needs to be controlled. It’s the operational capabilities that are to be manipulated to perform a smooth surgery even from a distant location. In this study, a robot system is being introduced for laparoscopic primary surgical tool insertion. It will incorporate a novel observer based dynamic control along with robot assisted bilateral control. Moreover, a virtual spring damper force lock system is introduced through which the slave system will notify the master regarding the target achieved and excessive force. The validation of the proposed control system is experimented with bilaterally controlled MU-LapaRobot. The experiment is comprising 3 cases of bilateral control criteria which are non-contact motion, contact motion, and limit force locking. The results defined the same value for contact and non-contact motion by 0.3N. The results depicted a force error of 3.6% and a position error of 5.8% which validated the proposed algorithm.